Pengaruh CR,ROE,dan DAR Terhadap Harga Saham Pada Perusahaan Sektor Pertambangan - Silfy Ayu Rahmawati; Titing Suharti; Diah Yudhawati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to determine the effect of Current Ratio (CR), Return On Equity (ROE), and Debt to Asset Ratio (DAR) on stock prices in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study used as many as 6 samples of mining sector companies listed on the IDX with a sampling method, namely purposive sampling.This research is a quantitative research using secondary data in the form of financial statements obtained from data that has been published by the Indonesia Stock Exchange and yahoo finance as well as other supporting data obtained from idnfinance. The analysis used in this study is panel data regression analysis, multiple linear regression, classical assumption test with hypothesis testing F test (simultaneous), t test (partial) and coefficient of determination (R2). The results of research conducted with panel data regression tests show that the best model used for this study is the Random Effect model.The results of the t test show that the variable Current Ratio (CR) has an insignificant effect on stock prices indicated by a significance value on CR of 0.9174 > 0.05, the variable Return On Equity (ROE) has a significant effect on stock prices indicated by a significance value on ROE of 0.0004 < 0.05, Debt To Asset ratio (DAR) has a significant effect on stock prices indicated by a significance value on DAR of 0.0000 < 0.05.Â Â Â